Prediction equations for the energy values of soybean meal for pigs at the growing phase with ex-post validation (Revista Ciência Agronômica, 2015)
The aim of this study was to determine and validate prediction equations for digestible (DE) and metabolizableenergy (ME) of soybean meal for growing pigs. The prediction equations were developed using data from chemical composition,digestibility and metabolizability of soybean meal samples (n = 25) evaluated in essays at Embrapa Suínos e Aves. The equationswere estimated through regression analysis, using the REG procedure of SAS and adjusted R² was the criterion of choice toselect the best models. Two equations were estimated for DE and two for ME. To validate the equations, one experimentwith two essays was performed to determine the values of DE and ME of five samples of soybean meal. In each essay, 24growing pigs with an initial weight of 54.20 ± 1.28 kg at first and 54.60 ± 2.26 kg at second essay, were sorted in a completerandomized block design with 6 treatments (1 reference diet and 5 test diets) and 4 replicates. Considering the lowest predictionerror (ep), the equations to predict the DE and ME of soybean meal were: DE = 48153 – 1586.1(PB) + 744.5(EE) + 363.6(FB)- 1398.3(MM) + 15.5(PB2) – 170.8(EE2) – 29.3(FB2) + 5.4(FDA2) – 2.5(FDN2) + 90.6(MM2) – 8.2(EEFDA) + 33(EEFDN),with R² = 0.88 and ep =2.32 and ME = 12692 – 2397.7(MM) – 56.8(EE2) + 164.9(MM2) – 102.2(EEFB) – 12.25(EEFDA)+ 67.6(EEFDN) + 5.5(PBFB) – 2.9(PBFDN) with R2 = 0.65 and ep= 1.69. Based on the chemical composition data andcorrelations, it was possible to establish prediction equations for the values of digestible and metabolizable energy of soybeanmeal for pigs, being necessary validation for greater accuracy of the models.